A new cryptic species of Nyctibatrachus (Amphibia, Anura, Nyctibatrachidae) with description of its tadpole from the central Western Ghats, India - Kumar, K.s. Pavan; Vishwajith, H.u.; Anisha, Anand; Dayananda, G.y.; Gururaja, Kotambylu Vasudeva; Priti, Hebbar (Zootaxa, 2022)
We describe a new species of night frog belonging to the genus Nyctibatrachus from the central Western Ghats, India. Nyctibatrachus tunga sp. nov. is distinguished from all congeners by a combination of (1) body size medium (SVL 37.0–40.2 mm ♂, 42.4–47.4 mm ♀), (2) head wider than long (HW 16.0–17.6 mm ♂, 17.4–20.3 mm ♀, HL 11.7–13.6 mm ♂, 13.4–15.5 mm ♀), (3) skin on dorsal and lateral surfaces with glandular folds and throat with dense glandular longitudinal folds, belly white, (4) webbing on toes medium, reaching the third subarticular tubercle on either side of fourth toe (5) presence of nuptial pad and femoral glands in adult males, (6) dorsal body color dark brown, ventrally buff colored except belly, (7) finger disc weakly developed (fd3 0.8±0.1 mm ♂, 1.0±0.1 mm ♀; fw3 0.5±0.1 mm ♂, 0.8±0.1 mm ♀), (8) toe disc moderately developed (td4 1.2±0.2 mm ♂, 1.6±0.1 mm ♀; tw4 0.8±0.1 mm ♂, 0.7±0.0 mm ♀), (9) third finger disc without dorso–terminal groove, fourth toe disc with dorso–terminal groove cover bifurcate distally. Further, molecular phylogeny based on two mitochondrial genes (16S rRNA and ND1), reveals that the new species is sister taxon to N. vrijeuni and N. shiradi. Based on the analysis of 16S rRNA, the new species is genetically divergent by 2.0% and 2.6% from N. vrijeuni and N. shiradi respectively indicating weak but consistent differences to these two species. The bioacoustic analysis also indicated that the new species differed from one of its closest congeners, N. vrijeuni by a higher dominant frequency in advertisement calls. At present, Nyctibatrachus tunga sp. nov. is known from streams within evergreen forests and coffee estates of the upper catchment areas of river Tunga in central Western Ghats.